An optimized fast-repetition-rate fluorometry method reveals photochemical flux bottlenecks in C3 photosynthesis that limit carboxylation and growth - Gennady Ananyev; Marie-Claire ten Veldhuis; Apostolos Zournas; Colin Gates; G. Charles Dismukes (Molecular Plant, 2026)

Extreme light acclimation reveals inherent photoprotective mechanisms in a natively low-light Chlorella - Grant Steiner; Devinjeet Saini; Colin Gates (Algal Research, 2026)

Chloride dependence of photosystem II operation in the hypercarbonate-requiring cyanobacterium Limnospira maxima - Leslie Castillo; Nidhi Patel; Stavroula Nicolaou; Nicole Seliga; Colin Gates (Photosynthesis Research, 2026)

Adaptation of the Chlorella photosynthetic electron transport chain to environmental light conditions - Grant Steiner; Devinjeet Saini; Arivu Kapoor; Colin Gates (Algal Research, 2025)

Exceptional Quantum Efficiency Powers Biomass Production in Halotolerant Algae Picochlorum sp.^ - Colin Gates; Gennady Ananyev; Fatima Foflonker; Debashish Bhattacharya; G. Charles Dismukes (Photosynthesis Research, 2024)

How chloride functions to enable proton conduction in photosynthetic water oxidation: Time-resolved kinetics of intermediates (S-states) in vivo and bromide substitution - Colin Gates; Jonah M. Williams; Gennady Ananyev; G. Charles Dismukes (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2023)

The effects of CdSe/ZnS quantum dots on the photosynthesis rate of the Chlorella Vulgaris beads - Wimeth Dissanayake; Richard Hailstone; Leslie Castillo; Fateme “Sara” Nafar; Mengdi Bao; Ruo-Qian Wang; Colin Gates; Xin Yong; Ke Du (Algal Research, 2023)

Regulation of light energy conversion between linear and cyclic electron flow within photosystem II controlled by the plastoquinone/quinol redox poise - Colin Gates; Gennady Ananyev; Shatabdi Roy-Chowdhury; Petra Fromme; G. Charles Dismukes (Photosynthesis Research, 2023)

Proximity-based proteomics reveals the thylakoid lumen proteome in the cyanobacterium Synechococcus sp. PCC 7002 - Kelsey K. Dahlgren; Colin Gates; Thomas Lee; Jeffrey C. Cameron (Photosynthesis Research, 2021)
Cyanobacteria possess unique intracellular organization. Many proteomic studies have examined different features of cyanobacteria to learn about the intracellular structures and their respective functions. While these studies have made great progress in understanding cyanobacterial physiology, the conventional fractionation methods used to purify cellular structures have limitations; specifically, certain regions of cells cannot be purified with existing fractionation methods. Proximity-based proteomics techniques were developed to overcome the limitations of biochemical fractionation for proteomics. Proximity-based proteomics relies on spatiotemporal protein labeling followed by mass spectrometry of the labeled proteins to determine the proteome of the region of interest. We performed proximity-based proteomics in the cyanobacterium Synechococcus sp. PCC 7002 with the APEX2 enzyme, an engineered ascorbate peroxidase. We determined the proteome of the thylakoid lumen, a region of the cell that has remained challenging to study with existing methods, using a translational fusion between APEX2 and PsbU, a lumenal subunit of photosystem II. Our results demonstrate the power of APEX2 as a tool to study the cell biology of intracellular features and processes, including photosystem II assembly in cyanobacteria, with enhanced spatiotemporal resolution.

Analysis of G ambierdiscus transcriptome data supports ancient origins of mixotrophic pathways in dinoflagellates - Dana C. Price; Natalie Farinholt; Colin Gates; Alexander Shumaker; Nicole E. Wagner; Paul Bienfang; Debashish Bhattacharya (Environmental Microbiology, 2016)
Summary Toxic dinoflagellates pose serious threats to human health and to fisheries. The genus Gambierdiscus is significant in this respect because its members produce ciguatoxin that accumulates in predominantly tropical marine food webs and leads to ciguatera fish poisoning. Understanding the biology of toxic dinoflagellates is crucial to developing control strategies. To this end, we generated a de novo transcriptome library from G. caribaeus and studied its growth under different culture conditions to elucidate pathways of carbon (C) and nitrogen (N) utilization. We also gathered available dinoflagellate transcriptome data to trace the evolutionary history of C and N pathways in this phylum. We find that rather than being specific adaptations to the epiphytic lifestyle in G. caribaeus , the majority of dinoflagellates share a large array of genes that putatively confer mixotrophy and the ability to use N via the ornithine‐urea cycle and nitric oxide synthase production. These results suggest that prior to plastid endosymbiosis, the dinoflagellate ancestor possessed complex pathways that linked metabolism, intercellular signaling, and stress responses to environmental cues that have been maintained by extant photosynthetic species. This metabolic flexibility likely explains the success of dinoflagellates in marine ecosystems and may presage difficulties in controlling the spread of toxic species.